Women's experience with home-based self-sampling for human papillomavirus testing. Issue 1 (December 2015) - Sultana, Farhana; Mullins, Robyn; English, Dallas; Simpson, Julie; Drennan, Kelly; Heley, Stella; Wrede, C.; Brotherton, Julia; Saville, Marion; Gertig, Dorota
Abstract Background Increasing cervical screening coverage by reaching inadequately screened groups is essential for improving the effectiveness of cervical screening programs. Offering HPV self-sampling to women who are never or under-screened can improve screening participation, however participation varies widely between settings. Information on women's experience with self-sampling and preferences for future self-sampling screening is essential for programs to optimize participation. Methods The survey was conducted as part of a larger trial ("iPap") investigating the effect of HPV self-sampling on participation of never and under-screened women in Victoria, Australia. Questionnaires were mailed to a) most women who participated in the self-sampling to document their experience with and preference for self-sampling in future, and b) a sample of the women who did not participate asking reasons for non-participation and suggestions for enabling participation. Reasons for not having a previous Pap test were also explored. Results About half the women who collected a self sample for the iPap trial returned the subsequent questionnaire (746/1521). Common reasons for not having cervical screening were that having Pap test performed by a doctor was embarrassing (18 %), not having the time (14 %), or that a Pap test was painful and uncomfortable (11 %). Most (94 %) found the home-based self-sampling less embarrassing, less uncomfortable (90 %) and more convenient (98 %) compared with their last Pap test experience (if they had one); however, many were unsure about the test accuracy (57 %). Women who self-sampled thought the instructions were clear (98 %), it was easy to use the swab (95 %), and were generally confident that they did the test correctly (81 %). Most preferred to take the self-sample at home in the future (88 %) because it was simple and did not require a doctor's appointment. Few women (126/1946, 7 %) who did not return a self-sample in the iPap trial returned the questionnaire. Their main reason for not screening was having had a hysterectomy. Conclusions Home-based self-sampling can overcome emotional and practical barriers to Pap test and increase participation in cervical screening despite some women's concerns about test accuracy. Mailing to eligible women and assuring women about test accuracy could further optimize participation in screening.